2020
DOI: 10.1111/liv.14519
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible factor 2α drives hepatosteatosis through the fatty acid translocase CD36

Abstract: Background & Aims: Molecular mechanisms by which hypoxia might contribute to hepatosteatosis, the earliest stage in non-alcoholic fatty liver disease (NAFLD) pathogenesis, remain still to be elucidated. We aimed to assess the impact of hypoxia-inducible factor 2α (HIF2α) on the fatty acid translocase CD36 expression and function in vivo and in vitro. Methods: CD36 expression and intracellular lipid content were determined in hypoxic hepatocytes, and in hypoxic CD36-or HIF2α-silenced human liver cells. Histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
4
19
0
Order By: Relevance
“…Notably, it has been recently reported that hepatocyte-specific Srebp1 downregulation did not affect expression of genes involved in FFA uptake as Cd36 in mouse livers (30). In addition, we have just demonstrated that both CD36 expression and triglyceride content increased in mouse and human liver cells under hypoxic conditions and that silencing HIF2A gene markedly suppressed both CD36 gene upregulation and lipid accumulation in hepatocytes (14). The novelty of our present study is that both CD36 expression and the degree of steatosis are increased in livers from animal models of IH and in patients with OSA featured by nocturnal IH, supporting the notion that CD36 could be a key factor driving hepatosteatosis in OSA patients.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Notably, it has been recently reported that hepatocyte-specific Srebp1 downregulation did not affect expression of genes involved in FFA uptake as Cd36 in mouse livers (30). In addition, we have just demonstrated that both CD36 expression and triglyceride content increased in mouse and human liver cells under hypoxic conditions and that silencing HIF2A gene markedly suppressed both CD36 gene upregulation and lipid accumulation in hepatocytes (14). The novelty of our present study is that both CD36 expression and the degree of steatosis are increased in livers from animal models of IH and in patients with OSA featured by nocturnal IH, supporting the notion that CD36 could be a key factor driving hepatosteatosis in OSA patients.…”
Section: Discussionsupporting
confidence: 46%
“…In particular, Greco et al showed that hepatic CD36 mRNA levels correlated with liver fat content in morbidly obese patients (11). In addition, different clinical studies have convincingly shown that the amount of both CD36 mRNA and protein was higher in the livers of biopsy-proven NAFLD patients than in subjects with histologically normal liver (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the role of HIFs on hepatosteatosis setup, some experimental studies revealed that both HIF1α and HIF2α were involved in hypoxia-induced lipid accumulation in hepatocytes, whereas other studies showed HIF2α as the major regulator of hepatic lipid metabolism because the absence of HIF2α, but not HIF1α, protected against lipid accumulation in the livers from mice lacking the Vhl gene (18,19). Supporting the latter, we have just demonstrated that HIF2α induced CD36 expression and function, the major driver of FFA uptake, triggering lipid accumulation in hepatocytes in vitro and in vivo, thus contributing to the hepatosteatosis onset (20). In this line, it has been demonstrated that the development of steatosis in hypoxic HepG2 cells is a consequence of increased HIF2α, which upregulated the hepatic expression of the adipose differentiationrelated protein (ADRP), also involved in FFA uptake (21).…”
Section: Molecular and Cellular Consequences Of Hypoxia On Hepatosteasupporting
confidence: 67%
“…Regarding HIF2α, a recent study revealed that IH exacerbated hepatosteatosis in mice fed HFD, which showed hepatic HIF2α overexpression along with a decreased β-oxidation and an enhanced de novo lipogenesis (22). Interestingly, silencing of hif-2α reduced lipid accumulation in hypoxic hepatocytes (20,22), pointing out to HIF2α as a key driver in hepatosteatosis setup. Recently, we have observed an upregulated expression of CD36, together with an increased triglyceride content, in livers from mice exposed to IH, pointing out that IH may also modulate FFA uptake (32).…”
Section: Experimental Evidences Linking Intermittent Hypoxia To Nafldmentioning
confidence: 99%
“…Moreover, it has been demonstrated that hypoxia-inducible factors (HIFs) also modulate CD36 expression 103,104 . Particularly, HIF2α upregulated CD36 expression and function triggering lipid accumulation in hepatocytes in vitro and in vivo, thus contributing to the onset of hepatosteatosis, the earliest phase of NAFLD 105 .…”
Section: Regulation Of Cd36 Expression and Function In Liver Cellsmentioning
confidence: 99%